International practice of state support of bioenergy development - Tasmaganbetov А.; Yessengeldin, B.; Tleubergenova, M.; Таsmaganbetova S. (BUKETOV BUSINESS REVIEW, 2023)
Object: The article examines the international practice of bioenergy development taking into account economic, social and environmental factors. The authors of the article focus on energy security during the use of biomass under changing operating conditions and restrictions. Methods: In the course of the study, statistical and comparative analysis methods were used to identify the effectiveness of the state policy on the introduction of bioenergy. To apply these methods, a literature review was conducted and statistical data from the International Renewable Energy Agency were used. Findings: The article analyzes the scientific works of scientists devoted to biomass and bioenergy, as well as state support tools used for the development of bioenergy. The authors have identified the main directions of bioenergy development that contribute to the achievement of economic, environmental and social goals. Conclusions: In international practice, the introduction of many bioenergy options depends on government support, taking into account the associated environmental benefits and existing government support for fossil fuels. There are two main forms of state support tools for bioenergy: preferential tariffs for specific technologies and general financial incentives. When implementing the bioenergy development policy, it is necessary to take into account the availability of raw materials from biomass and the specific features of the country’s energy sector. The main factor is the availability of bioenergy technologies, so it is necessary to pay attention to access to networks and standardization of raw materials.